The Basic Steps of Land Surface Temperature Determination Using Thermal Images of Landsat-7 (Damascus University Journal of arts and humanities sciences, 2021)
Land Surface Temperature (LST) is one of the most important variables measured by satellite remote sensing data, where the thermal images present a great potential for providing information on spatial and temporal changes in LST. Many methodologies have been developed for calculation the LST from the space. However, estimating LST is still a complex task since the beginning of its retrieval. This research aims to establish the basic steps for calculating the LST from the thermal data of Landsat-7. A brief theoretical background of the subject is reviewed to explain the concepts entre the LST and the thermal sensor, followed by the methodological framework used to derive the LST from the satellite data with an applied illustration on Cairo city.
Keywords: Land Surface Temperature (LST); Landsat-7; Radiometric calibration; Atmospheric correction; Emissivity